The Governance Gap And Its Implications For Destination Image And Tourist Satisfaction: A Marine Ecotourism Study In The Likupang And Bunaken - Farid; Ahmad AB; Muaz Azinuddin (International Journal of Education Management and Religion, 2026)
Marine ecotourism destinations possess significant economic potential but face concurrent sustainability challenges, including environmental degradation and tourist dissatisfaction. This study investigates the interplay among destination image, tourist satisfaction, and governance failures within Indonesia's Super Priority Tourism Destinations, specifically Likupang and Bunaken. Employing a qualitative phenomenological approach, this study explores the lived experiences of key stakeholders, including tourists, community members, industry operators, and academic experts, through in-depth interviews and observation. The findings reveal a significant governance gap: a disconnect between top-down development policies and on-the-ground operational realities. This gap manifests as tangible failures, including poor waste management, inconsistent service quality, and inadequate community empowerment. These factors collectively create an expectation-reality paradox that fundamentally undermines the destination image and degrades tourist satisfaction, thereby threatening the long-term viability of both sites. This study proposes a constructive governance model for sustainable marine ecotourism as its primary contribution. This model advocates a shift from a sectoral, top-down approach to a collaborative framework, specifically through a Public-Private Partnership (PPP) scheme. The proposed model aims to align economic incentives with conservation objectives by integrating pro-environmental behaviors and authentic community participation, providing a viable pathway to restore the destination image and ensure sustained tourist satisfaction.